Platypnea-orthodeoxia syndrome: an unusual cause of breathlessness in late pregnancy. (November 2020) - Silvani, A.; Bucalo, F.; Voekt, C.; Tobler, D.; Girard, T.
Highlights: Breathlessness in late pregnancy is not infrequent. The differential diagnosis can be challenging. Platypnea-orthodeoxyia syndrome is rare, but can be diagnosed easily. Positional oxygen desaturation in the upright position is pathognomonic. Abstract: A pregnant patient with shortness of breath and arterial oxygen desaturation is presented. The primary and tentative initial diagnosis was pulmonary embolism. Her desaturation and dyspnea were aggravated in the upright compared with the supine position. The minimal response to supplemental oxygen suggested right-to-left shunting, which was confirmed by echocardiography. Shunting was minimal in the supine and maximal in the upright position, leading to the diagnosis of platypnea-orthodeoxia syndrome. By two weeks postpartum the patient's symptoms had resolved and shunting was undetectable.